2021
DOI: 10.1080/00346764.2021.1894350
|View full text |Cite
|
Sign up to set email alerts
|

(Online) manipulation: sometimes hidden, always careless

Abstract: Ever-increasing numbers of human interactions with intelligent software agents, online and offline, and their increasing ability to influence humans have prompted a surge in attention toward the concept of (online) manipulation. Several scholars have argued that manipulative influence is always hidden. But manipulation is sometimes overt, and when this is acknowledged the distinction between manipulation and other forms of social influence becomes problematic. Therefore, we need a better conceptualisation of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…This paper aims to contribute to this new research angle and strengthen the critical perspective on algorithmic transparency that Wang (2022Wang ( , 2023 championed. To do so, I show that the risk concerning algorithmic transparency's manipulative potential can be understood with the indifference view of manipulation (Klenk 2020(Klenk , 2021b. The indifference view explains better why algorithmic transparency has manipulative potential.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This paper aims to contribute to this new research angle and strengthen the critical perspective on algorithmic transparency that Wang (2022Wang ( , 2023 championed. To do so, I show that the risk concerning algorithmic transparency's manipulative potential can be understood with the indifference view of manipulation (Klenk 2020(Klenk , 2021b. The indifference view explains better why algorithmic transparency has manipulative potential.…”
Section: Introductionmentioning
confidence: 95%
“…Next to several counterexamples that challenge the covertness criterion (see especially Barnhill 2014), there are also fundamental moral and conceptual reasons against that criterion. For instance, Klenk (2021b) suggested that the criterion may imply that responsibility for manipulation is shifted toward the victim in problematic ways. After all, an influence counts as manipulation, according to the vulnerability view, only insofar as it remains hidden.…”
Section: The Vulnerability View Is Itself Problematicmentioning
confidence: 99%
“…There is agency on both sides, the users and the platforms, and there is an intertwining of how users affect platforms and vice-versa. The users can affect each other's beliefs; they can hijack the platforms and turn these into places of political activism and resistance (Cammaerts, 2015) for their own purposes while at the same succumbing to nudging and manipulation exerted by the SN platforms (Klenk, 2022). The user's epistemic agency is constrained and shaped by the environments in which they find themselves.…”
Section: Operationalising the Epistemic Agency Of Users Through A Sit...mentioning
confidence: 99%
“…Nonetheless, there is a bridge between accounts of manipulative behaviour and manipulated behaviour. On my preferred analysis of manipulative behaviour, manipulation is a kind of negligence in revealing reasons to others (Klenk 2021a(Klenk , 2021b. A manipulator is negligent in the sense that they ultimately choose their means of infuence because it is efective in getting the manipulatee to believe, feel, or desire in a certain way and not because it reveals reasons to the manipulatee.…”
Section: Manipulated and Manipulative Behaviourmentioning
confidence: 99%